2009
DOI: 10.1111/j.1365-2672.2009.04315.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proteus vulgaris growth on the establishment of a cheese microbial community and on the production of volatile aroma compounds in a model cheese

Abstract: Aims:  To investigate the impact of Proteus vulgaris growth on a multispecies ecosystem and on volatile aroma compound production during cheese ripening. Methods and Results:  The microbial community dynamics and the production of volatile aroma compounds of a nine‐species cheese ecosystem were compared with or without the presence of P. vulgaris in the initial inoculum. Proteus vulgaris was able to colonize the cheese surface and it was one of the dominant species, representing 37% of total isolates at the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
1
32
0
1
Order By: Relevance
“…First, the Gram-negative bacterial microbiota was associated with hygienic problems, but more recently an interest in their role in flavour production has been reported [11]. In the present study, a significant Gram-negative bacterial microbiota consisting of Proteus vulgaris and Alcaligenes faecalis was found on cheese from dairy C. A previous study has focused on P .…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…First, the Gram-negative bacterial microbiota was associated with hygienic problems, but more recently an interest in their role in flavour production has been reported [11]. In the present study, a significant Gram-negative bacterial microbiota consisting of Proteus vulgaris and Alcaligenes faecalis was found on cheese from dairy C. A previous study has focused on P .…”
Section: Discussionsupporting
confidence: 47%
“…The presence of Gram-negative bacteria was first hypothesised to be indicative of hygienic problems. However, more recent results have shown that they produce important cheese flavour compounds and thus might contribute positively to the cheese ripening process [11]. Several studies have characterised the cheese microbiota by both culture-dependent methods and -independent methods [43].…”
Section: Introductionmentioning
confidence: 99%
“…In some of the studies, the synergistic effects of Y. lipolytica with other microorganisms and, in particular, with D. hansenii have been stressed (De Wit et al, 2005;Freitas et al, 1999;Wyder et al, 1999). Finally, Y. lipolytica is repeatedly included in complex, experimental cheese communities containing multiple bacterial, fungal and yeast species (Deetae et al, 2009;DelbesPaus et al, 2012;Irlinger et al, 2012;Martin et al, 2001). …”
Section: Natural Occurrence Of Yarrowia Lipolytica In Foodmentioning
confidence: 99%
“…Propionibacterium spp., in particular P. freudenreichii are known as an exopolysaccharide producer (Deutsch, Falentin, Dols-Lafargue, LaPointe, & Roy, 2008) that therefore can contribute to smearyness of the cheese surface and to off-flavor due to propionate production as well as to blowing of the foil-package through gas formation. P. vulgaris is a Gramnegative opportunistic pathogen with swarming ability and a potential contributor to off-flavor due to indole production and its potential to produce volatile compounds in large variety (Deetae, Bonnarme, Spinnler, & Helinck, 2007;Deetae et al, 2009).…”
Section: Microorganisms Isolated From Red-smear Cheese Surfacementioning
confidence: 99%